Utilization of Technology in Learning Process Management in Industrial Engineering Vocational High Schools - Warkianto Widjaja (Universitas Pendidikan Ganesha, 2025)
The lack of use of technology media among industrial engineering students of vocational high schools. Multimedia elements are expected to provide innovation in the learning process with the support of components. However, the use of technological elements such as text and images sometimes hinders the learning process for both teachers and students. Urgent to be studied because there is a difference between expectations and reality in the field. The aim is to evaluate the use of technology components from three devices, namely Multimedia, digital and tablets and to determine the correlation of the three variables. The research approach is quantitative survey type. The number of samples is 127 people, namely industrial engineering students and teachers. Data collection techniques with instruments that have been developed from multimedia variable indicators, digital stories and tablets. The instrument is assessed based on a Likert scale from point 1 to point 5. The data analysis technique uses descriptive statistics assisted by SPSS Version 29.0, with validation tests, means, standard deviations and minimum values and correlations. The results found that the use of multimedia, digital, and tablets has high reliability and correlation as well as a positive and significant relationship to all variables in the evaluation. The findings confirm that the components in multimedia are in the high category and can be used in an effective learning process. The implications provide an overview for industrial engineering teachers and students to actively use multimedia as a learning process aid in the classroom.